Development of a three-dimensional virtual monitoring system for a workshop. (November 2020) - Li, Jiang; Gao, Kunshan; Yu, Cungui; Zhou, Cheng
Abstract: Aiming at the problems of poor applicability and development efficiency of the current manufacturing workshop monitoring system, a workshop monitoring system using the industrial Internet of Things platform as the system service platform is proposed. This article takes a seal automated production line as an example to illustrate the development process of a workshop monitoring system, including virtual scene construction, data acquisition and real-time model driving based on the industrial Internet of Things platform. The results show that the 3D virtual monitoring system has good real-time performance and realizes multi-level and visual monitoring. It has certain reference value for the development of the workshop 3D virtual monitoring system.